Atrial fibrillation in older inpatients: are there any differences in clinical characteristics and pharmacological treatment between the frail and the non‐frail?. Issue 1 (27th January 2016) - Nguyen, T. N.; Cumming, R. G.; Hilmer, S. N.
Abstract: Background: Frailty is common in patients with atrial fibrillation and may impact on antithrombotic and anti‐arrhythmic treatment. Aim: To describe differences in clinical characteristics, prescription of antithrombotic and anti‐arrhythmic medications and incidence of haemorrhage and stroke, between frail and non‐frail older inpatients. Methods: Prospective observational study in patients aged ≥65 years with atrial fibrillation admitted to a teaching hospital in Sydney, Australia. Frailty was assessed using the Reported Edmonton Frail Scale, stroke risk with CHA2DS2‐VASc score and bleeding risk with HAS‐BLED score. Participants were followed after 6 months for haemorrhages and strokes. Results: We recruited 302 patients (mean age 84.7 ± 7.1 years, 53.3% frail, 50% female, mean CHA2DS2‐VASc 4.61 ± 1.44, mean HAS‐BLED 2.97 ± 1.04). Frail participants were older and had more co‐morbidities and higher risk of stroke but not haemorrhage. Upon discharge, 55.7% participants were prescribed with anticoagulants (49.3% frail, 62.6% non‐frail, P = 0.02). Thirty‐three per cent received antiplatelets only and 11.1% no antithrombotics, with no difference by frailty status. For anti‐arrhythmics, 52.6% received rate‐control drugs only, 11.8% rhythm‐control drugs only and 13.5% both and 22.1% were not prescribed either, with no difference by frailty status. On univariate logistic regression, frailty decreased the likelihood of anticoagulant prescription (odds ratio (OR) 0.58, 95%CI 0.36–0.93), but this was not significant on multivariate analysis (OR 0.66, 95%CI 0.40–1.11). After 6 months, overall incidence of ischaemic stroke was 2.1%, and in patients taking anticoagulants, incidence of major/severe bleeding was 6.3%, with no significant difference between frailty groups. Conclusions: Frailty status had little impact on antithrombotic prescription and no impact on anti‐arrhythmic prescription.